Kingdom of the Netherlands : Aruba; Detailed Assessment of Compliance with the Basel Core Principles for Effective Banking Supervision. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This paper discusses detailed assessment of compliance with the Basel Core Principles for effective banking supervision for the Kingdom of the Netherlands-Aruba. Aruba's offshore banking sector is small by international standards, with only two institutions registered. The mission also recommends that the Central Bank of Aruba (CBA) meet with management to better understand their plans for their Aruban operations and their financial results. Aruba remains open to foreign investment and migrant workers, who make up 40 percent of the population and have been key contributors to economic growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet